ANALISIS PERKEMBANGAN SOSIAL EMOSIONAL TERCAPAI DAN TIDAK TERCAPAI SISWA KELAS IV SEKOLAH DASAR ISLAM TERPADU INSAN SEJAHTERA - Redhiana Langen Tresna, - (2022)
ANALYSIS OF SOCIAL EMOTIONAL DEVELOPMENT ACHIEVED AND NOT ACHIEVED IN CLASS IV INTEGRATED ISLAMIC ELEMENTARY SCHOOL INSAN SEJAHTERA ABSTRACT This study aims to determine 1) Social emotional development is achieved by fourth grade students of SD IT Insan Sejahtera in learning, 2) Social emotional development is not achieved by fourth grade students of SD IT Insan Sejahtera in learning, 3) How are the teacher's efforts in developing students' social emotional fourth grade SD IT Insan Sejahtera. This study uses a descriptive qualitative approach with the type of case study research. The research subjects are students and homeroom teachers. Research data collection techniques were obtained through observation, interviews/questionnaires and field notes. While the data analysis from the results of this study, was carried out based on descriptive analysis, the analysis consisted of three interacting analysis lines, namely data reduction, data presentation, and drawing conclusions. Conclusion Data analysis is first, students' emotional social development is achieved in learning, namely students show caring, participatory, communicative, interactive attitudes, able to show a sense of cooperation in study groups Able to show self-confidence during the learning process, second, students' social emotional development not achieved in learning, namely students do not show a quiet attitude, students are able to adapt well there are no difficulties, students are able to get along with other students without being covered up, in learning students do not choose friends, there are no difficulties in communicating, students show less commendable attitudes such as playing with friends excessively and when communicating still often use dirty or less commendable words. The three teacher's efforts in developing the socio-emotional emotions of students are creating character guidance every week and making Up Skill programs at school, arranging seating strategies and study friends according to the heterogeneity of students' emotional abilities and providing an approach in the form of motivation so that they can take part in school activities in the form of competitions. competitions and extracurricular activities. Keywords: Analysis, Development social-emosional